Content Validity in Android-Based Augmented Reality Media for High School Science Students on Covalent Bonds Topic: Rasch Model Analysis - Sri Yamtinah*; Mega Candra Dewi; Nanik Dwi Nurhayati; Endang Susilowati; Isma Aziz Fakhrudin; Dimas Gilang Ramadhani; Ari Syahidul Shidiq; Sulistyo Saputro (Jurnal Pendidikan Sains Indonesia, 2022)
The 21st-century chemistry learning that teaches abstract and complex concepts needs to develop learning media that can increase students' learning motivation and visualize abstract concepts in chemistry. One of the media in the 21st century developed in this study is Android-based augmented reality media. The purpose of this study was to test the validity of the Android-based Augmented Reality media and see the differences in perceptions between teachers and students in assessing media. The validation of android-based Augmented Reality learning media uses a questionnaire and is quantitative. The Rater for assessing the product consisted of 6 senior chemistry teachers at 5 different schools in Surakarta and 20 students who had obtained the material for covalent bonding at SMA N 1 Ngemplak Boyolali. The data obtained were analyzed by Rasch Model using Facets software. The results of the analysis show that exact agreements are 35.1% and exacted agreements are 35.2%. This happens because the aspects are considered easy by the teacher, but the students consider these aspects difficult. The aspect or item that is considered the most difficult to achieve is the suitability of the example with the material and improving understanding of the material. Based on this research, in developing media, it must be packaged properly so that it is easily understood and understood by students